2010
DOI: 10.1017/s0029665109993600
|View full text |Cite
|
Sign up to set email alerts
|

Improved compliance and increased intake of energy and protein with a high energy density, low volume multi-nutrient supplement

Abstract: Although it is often hypothesised that higher energy density liquid supplements will have a greater effect on total nutritional intake than standard supplements, there have been few comparative studies in clinical settings (1) . This study aimed to compare the effects of a low volume, high energy density (2.4 kcal/ml) liquid oral nutritional supplement (ONS) versus standard ONS (1.5-2.0 kcal/ml) on food and total energy and protein intakes and patients' compliance with supplementation.A longitudinal study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 2 publications
2
13
1
1
Order By: Relevance
“…The energy density, volume and macronutrient profile of the supplement, the time and way in which it is administered and the duration of supplementation are factors that may affect compliance (12,52) . Recently, studies have suggested that increasing the energy density of liquid feeds improves both nutritional intake and compliance with supplementation, over the use of standard energy dense feeds in hospital and community patients (53)(54)(55) . Increasing the energy density of ONS minimises the volume needed to be consumed by a malnourished patient, and so encourages compliance and nutritional intake (53)(54)(55) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 1 more Smart Citation
“…The energy density, volume and macronutrient profile of the supplement, the time and way in which it is administered and the duration of supplementation are factors that may affect compliance (12,52) . Recently, studies have suggested that increasing the energy density of liquid feeds improves both nutritional intake and compliance with supplementation, over the use of standard energy dense feeds in hospital and community patients (53)(54)(55) . Increasing the energy density of ONS minimises the volume needed to be consumed by a malnourished patient, and so encourages compliance and nutritional intake (53)(54)(55) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Recently, studies have suggested that increasing the energy density of liquid feeds improves both nutritional intake and compliance with supplementation, over the use of standard energy dense feeds in hospital and community patients (53)(54)(55) . Increasing the energy density of ONS minimises the volume needed to be consumed by a malnourished patient, and so encourages compliance and nutritional intake (53)(54)(55) . It is also likely that encouragement and education about the reasons for taking supplements would be beneficial.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…A esto, se le suma que en los últimos trabajos sobre adherencia terapéutica, únicamente se encontraron herramientas estandarizadas para el tratamiento farmacológico, mientras que para el estudio del cumplimiento en la ingesta de suplementos nutricionales y nutrición enteral se siguen utilizando métodos indirectos no estandarizados (16); encontrando algunos trabajos que utilizan el conteo del número de envases consumidos, medir la cantidad de producto restante para determinar las calorías ingeridas al día y otros como es el uso de registros o diarios dietéticos de cinco días, métodos útiles pero no libres de sesgos importantes como es introducir en los resultados la propia sobreestimación del paciente (16)(17)(18).…”
Section: Discussionunclassified
“…Small volume, high energy density, and high nutrient density were shown to improve ONS compliance (Hubbard, Buchan, Sanders, Brothers, & Stratton, 2010;Hubbard et al, 2012;Nieuwenhuizen, Weenen, Rigby, & Hetherington, 2010). In addition, Nieuwenhuizen et al (2010) reported a positive influence of liquid format and general palatability on ONS compliance in a group of care home living ONS users.…”
Section: Introductionmentioning
confidence: 91%